گۆرانكاری بەكارهێنانی زەوی و كاریگەری لە سەر رێكردنی ئاو لە ئاوزێڵەکانی خۆر ئاوای شاری سلێمانی لە نێوان ساڵانی 1999-2019 - عزیز, پاكیزە سعید (Sulaimani Journal for Humanities, 2021)
Land change is the main factor that impacts surface runoff processes. This paper replies on many forms of data and different methods to indicate the rate of surface flow alterations due to the expansion of slemani city between 1999 and 2019. Human activity has caused changes in land uses throughout the city which led to the decrease of infiltration levels and an increase in surface runoff. The extensive use of impervious materials has directly resulted in an increase of 24.9% in surface runoff.